Compiling a Sharia Indicators of Wedding Organiser - Arip Rahman; Muhammad Yusuf Ibrahim; Aisyah As-Salafiyah; Rusdi Hamka Lubis; Andi Iswandi (Perisai : Islamic Banking and Finance Journal, 2022)
The sharia wedding organizer industry is starting to provide an alternative sharia version. However, no specific index can be used as a standard for sharia compliance of a wedding organizer. This study aims to compile a sharia wedding organizing index from the perspective of Maqashid Sharia. The sharia wedding organizer index can then be used as an indicator in viewing the sharia wedding organizer. By using a literature review method, this study will collect literature in the form of postulate and previous studies as a basis for compiling an index. In calculating the weights, this study uses the Simple Additive Weighting approach. The primary basis for compiling the index is the Maqashid Sharia index theory by Al-Ghazali. The findings show that 13 indicators are used as indexes that measure the sharia of the wedding organizer. The indicators are seclusion, tradition, pre-wedding, make-up artist, prayer time, eating etiquette, food, fashion style, contract form, package options, transaction medium, music, and marriage motivations. This study is the first to compile a list of sharia requirements and rules that sharia wedding organizers must meet.